Evaluación funcional de espermatozoides posterior a la separación por columnas magnéticas - Gómez Morales, Ana Itzel (Universidad Autónoma Metropolitana, 2020)
El análisis de varianza revela la diferencia estadísticamente significativa del modelo lineal corregido (p<0.025) con potencia observada ≈ 80% y la varianza del término de error es constante en la combinación de los niveles de los factores (Prueba de Levene, p=0.25). El procedimiento mostró un adecuado comportamiento en la explicación de la varianza de la media general (p<1x10-7) y de los tratamientos, pero no de la clasificación clínica y la interacción de los tratamientos-clasificación clínica. La proporción de espermatozoides apoptóticos obtenidos por el método de coctel de anticuerpos fue significativamente menor que los derivados por método convencional con MACS (Fc1gl= 5.04, p<0.03). La clasificación clínica de las muestras seminales no muestra diferencia significativa por lo que no sesga los resultados de la separación de los gametos apoptóticos por ambos métodos (p=0.94). No se reveló error de tipo IV (interpretación incorrecta del rechazo correcto de la hipótesis nula) por lo que no se observa efecto del experimentador en la evaluación de los resultados (p=0.76). El estado del acrosoma de los gametos obtenidos de la fracción negativa durante la separación magnética usando el coctel de anticuerpos tuvo un porcentaje del 98%. Después de la evaluación de 10,000 eventos, el 99% de los espermatozoides formaron agregados de JC-1 revelando incremento del potencial mitocondrial y sólo el 0.5% permanecieron de forma monomérica en la fracción negativa en contraste con el 90.8% de los gametos que formaron agregados y el 43.3% que permanecieron como monómeros en la fracción positiva. En conclusión, encontrar una intensidad de florescencia para cada receptor mayor en los donadores fértiles que en los pacientes infértiles nos sugiere que probablemente la apoptosis en el espermatozoide tenga que ser inducida por la concentración de receptores en membrana, por tanto, al ser baja la cantidad de estos, la intensidad de la señal se considera débil y por eso escapan al mecanismo de eliminación, sufriendo así de una apoptosis abortiva. MACS con el coctel de anticuerpos es mejor eliminando las células apoptóticas con ADN fragmentado en comparación con la técnica estándar, células que posteriormente pueden ser utilizadas para TRA. La combinación de MACS con centrifugación en gradiente de doble densidad produce una población limpia de espermatozoides caracterizada por una mayor movilidad, viabilidad y morfología. Además, los espermatozoides tratados por MACS muestran manifestaciones de apoptosis reducidas, incluida la fragmentación del ADN. En este contexto, MACS puede considerarse una técnica de preparación molecular única que complementa los protocolos convencionales de preparación de espermatozoides.; Infertility is a problem that affects one in six couples, of which up to 60% depends on the male factor. In the search for a non-invasive method that allows to solve the low success rates in assisted reproduction techniques, the implementation of a cocktail of apoptotic markers is proposed with the use of the MACS method that allows eliminating sperm with initial or early apoptosis and Final or late apoptosis, as well as the evaluation of the mitochondrial membrane potential to know the physiological state of the cell, the acrosomal reaction test with the purpose of obtaining sperm with a greater potential for fertilization. Therefore, the objective of the project was to evaluate the efficacy in the separation of apoptotic spermatozoa, in the early and late stages, present in the ejaculate of infertile patients (normozoospermic and astenozoospermic). Seminal samples of 74 infertile men and 10 fertile donors were included. A spermatobioscopy of each sample was performed, before and after the swim-up separation method. Two methods of magnetic separation were compared (conventional vs. cocktail of apoptotic markers). The proportion of gametes positive for TRAIL-R1, TRAIL-R2, Fas, VEGFR-1/Flt-1 and annexin V were evaluated in both methods. The results showed a significant difference in the percentage of spermatozoa positive for TRAIL-R1 in the samples of patients with infertility; low expression of the TRAIL-R1, TRAIL-R2, Fas, VEGF-R1 / Flt-1 and annexin V molecules in the sperm plasma membrane of infertile patients in contrast to fertile donors. With the exception of annexin V, which was located only in the middle piece, the immunofluorescence location of the receptors was in the middle piece and scourge. Once the separation was made for each type of MACS, the sperm viability showed a decrease in the separation by MACS COCTEL when the percentage of viable gametes from fertile donors obtained by the conventional method was contrasted (60% vs. 6%; p<0.01), in normozoospermic infertile patients (30% vs. 4.3%, p<0.01), but not in the samples of asthenozoospermic patients (32% vs. 55%, p<0.05). All comparisons showed a higher proportion of total mobile sperm using the conventional MACS separation method. It should be mentioned that, the proportion of progressive mobile sperm in the negative fractions of fertile donors was significantly higher during the separation performed by the conventional method in contrast to the antibody cocktail (49% vs. 15.8, p<0.01), infertile patients normozoospermic (47.5% vs. 22.5%, p<0.03) and astenozoospermic (66.5% vs. 19.5%, p<0.01), respectively. All comparisons showed a lower proportion of apoptotic sperm using the antibody cocktail separation method. The mean differential of the DFI in the negative-positive fraction ratio obtained by the antibody cocktail method showed a lower proportion of apoptotic gametes than that determined by the conventional method by MACS in the samples of fertile donors (-29.5% vs. -19 %, p<0.05), normozoospermic infertile patients (-34% vs. -9.3%, p<0.01), and in astenozoospermic patient samples (-40% vs. -9%, p<0.01). The analysis of variance reveals the statistically significant difference of the corrected linear model (p <0.025) with observed power ≈80% and the variance of the error term is constant in the combination of the factor levels (Levene's test, p=0.25 ). The procedure showed an adequate behavior in the explanation of the variance of the general mean (p<1x10-7) and of the treatments, but not of the clinical classification and the interaction of the treatments-clinical classification. The proportion of apoptotic sperm obtained by the antibody cocktail method was significantly lower than those derived by conventional method with MACS (Fc1gl= 5.04, p<0.03). The clinical classification of the seminal samples does not show a significant difference, so it does not bias the results of the separation of apoptotic gametes by both methods (p=0.94). No type IV error (incorrect interpretation of the correct rejection of the null hypothesis) was revealed, so no effect of the experimenter is observed in the evaluation of the results (p=0.76). The acrosome state of the gametes obtained from the negative fraction during magnetic separation using the antibody cocktail had a percentage of 98%. After the evaluation of 10,000 events, 99% of sperm formed aggregates of JC-1 revealing an increase in mitochondrial potential and only 0.5% remained monomerically in the negative fraction in contrast to 90.8% of the gametes that formed aggregates and 43.3% that remained as monomers in the positive fraction. In conclusion, finding a fluorescence intensity for each recipient greater in fertile donors than in infertile patients suggests that sperm apoptosis probably has to be induced by the concentration of membrane receptors, therefore, as the amount is low of these, the signal strength is considered weak and therefore they escape the elimination mechanism, thus suffering from an abortive apoptosis. MACS with the antibody cocktail is better by removing apoptotic cells with fragmented DNA compared to the standard technique, cells that can later be used for TRA. The combination of MACS with double density gradient centrifugation produces a clean sperm population characterized by increased mobility, viability and morphology. In addition, sperm treated by MACS show reduced manifestations of apoptosis, including DNA fragmentation. In this context, MACS can be considered a unique molecular preparation technique that complements conventional sperm preparation protocols.